Adolescent and puericulture - Del Ciampo, Luiz Antonio; Del Ciampo, Ieda Regina Lopes (Medicina (Ribeirao Preto), 2017)
From the nineteenth century, adolescence becomes aroused great interest in the society due to the process of economic, scientific and social development, which drives the creation of health services directed to the care of the people in the second decade of life. This article presents a brief history of Puericulture, the consolidation of Hebiatria and highlights the importance of services in an adolescent primary health care. Supported in some classic texts on the subject, it drew a parallel with the pioneer's paediatric health programs, to encouraging the actions of prevention and promotion of adolescent health at the primary level as a strategy to ensure healthy living conditions